2002
DOI: 10.1053/jhep.2002.36495
|View full text |Cite
|
Sign up to set email alerts
|

Recombinant alfa-interferon plus ribavirin therapy in children and adolescents with chronic hepatitis C

Abstract: Treatment with alfa-interferon alone yielded poor results in children with chronic hepatitis C and was not generally recommended. Owing to limited experience with combination therapy in children, the aim of the study was to evaluate the efficacy and tolerability of alfa-interferon 2b in combination with ribavirin in these patients with different routes of viral transmission. In an uncontrolled pilot study, 41 children and adolescents ranging from 3 to 16 years were treated with alfa-interferon at a dose of 3

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
79
0
3

Year Published

2005
2005
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 107 publications
(88 citation statements)
references
References 27 publications
6
79
0
3
Order By: Relevance
“…Our studies demonstrate that interferon alfa-2b in combination with oral ribavirin is effective and reasonably safe for the treatment of childhood chronic hepatitis C. Infection with HCV genotypes 2 or 3, and lower level of serum HCV RNA at baseline in HCV genotype 1, are associated with higher virological response rates. These results are consistent with those reported in small pediatric pilot [18][19][20][21] and large adult studies. 7,8 SVR rates in children with chronic HCV given interferon alfa-2b with ribavirin in these studies are higher than in those using interferon alone (46% vs. 36%, respectively).…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Our studies demonstrate that interferon alfa-2b in combination with oral ribavirin is effective and reasonably safe for the treatment of childhood chronic hepatitis C. Infection with HCV genotypes 2 or 3, and lower level of serum HCV RNA at baseline in HCV genotype 1, are associated with higher virological response rates. These results are consistent with those reported in small pediatric pilot [18][19][20][21] and large adult studies. 7,8 SVR rates in children with chronic HCV given interferon alfa-2b with ribavirin in these studies are higher than in those using interferon alone (46% vs. 36%, respectively).…”
Section: Discussionsupporting
confidence: 93%
“…Most events, such as insomnia, irritability, and somnolence, were mild to moderate in severity. In addition, depression, a side effect not previously reported in children with chronic HCV infection given interferon alone 23 or with ribavirin, [18][19][20][21] occurred in 13% of subjects. This may reflect the fact that the protocols were designed to identify and monitor depressive symptoms.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…14 Thyroid abnormalities following interferon therapy have also been described in children receiving interferon for hepatitis C infection. 15 Some of these complications of IFN␣ therapy, especially thyrotoxicosis, can be severe and may interfere with adequate interferon therapy in patients with hepatitis C. 13,[16][17][18] Moreover, because the symptoms of hypothyroidismsuch as fatigue, hair loss, myalgia, and weight gain-may be attributable to hepatitis C or IFN␣ therapy, 8 the diagnosis of hypothyroidism in these patients may be delayed. This delay may lead to development of further complications.…”
mentioning
confidence: 99%
“…Currently, the only Food and Drug Administration‐approved options for children with chronic HCV infection are ribavirin (RBV) and pegylated‐interferon (PEG‐IFN). While sustained viral responses (SVRs) have improved over the last several decades from ∼16% with IFN monotherapy to >50% with the combination of RBV and PEG‐IFN, multiple studies have shown that SVR rates remain frustratingly low compared to adults with access to DAA regimens 6, 13, 100, 101, 102, 103, 104, 105, 106, 107, 108, 109, 110, 111, 112, 113, 114, 115, 116. Consequently, in the absence of approved DAA therapies in the United States, the chance of attaining SVR in HCV‐infected children and adolescents is little more than 50% (Table 4).…”
Section: Managementmentioning
confidence: 99%